2008
DOI: 10.1111/j.1365-2249.2008.03655.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 12B gene polymorphism and apparent resistance to hepatitis C virus infection

Abstract: SummaryCellular immunity with interferon gamma production could have a role in protection from hepatitis C virus (HCV). Interleukin (IL)-12 is a key cytokine in promoting such anti-viral T helper 1 (Th1) responses. We hypothesized that a genetic background able to promote cellular responses may be associated with apparent protection from infection and have investigated the distribution of the functional 1188A/C polymorphism of IL-12B in HCV exposed but uninfected cases. The frequency of the high IL-12-producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Th1 cellular immune responses are important for effective clearance of HCV viraemia [18–21] and IL‐12 is considered a key cytokine in promoting a Th1 response. A functional single nucleotide polymorphism in IL12B gene has previously been found to be associated with this EU cohort [22]. However in this study IL‐12 levels were low in EU, which demonstrates the challenges with extrapolation of functional correlates from single nucleotide genetic associations.…”
Section: Discussionmentioning
confidence: 67%
“…Th1 cellular immune responses are important for effective clearance of HCV viraemia [18–21] and IL‐12 is considered a key cytokine in promoting a Th1 response. A functional single nucleotide polymorphism in IL12B gene has previously been found to be associated with this EU cohort [22]. However in this study IL‐12 levels were low in EU, which demonstrates the challenges with extrapolation of functional correlates from single nucleotide genetic associations.…”
Section: Discussionmentioning
confidence: 67%
“…A cohort of current IDU not known to have HCV infection or other blood borne viruses was recruited between 2003 and 2014 from a variety of locations in Plymouth, UK, as previously described . All individuals completed a confidential structured questionnaire to collect demographic data and a detailed injecting history.…”
Section: Methodsmentioning
confidence: 99%
“…EU cohorts are immunologically distinct from both healthy controls and those who spontaneously clear HCV infection (see Table ) . Up to 60% of EU individuals display HCV‐specific adaptive T‐cell responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inheritance of specific gene variants may alter the direction of immune responses and affect the pathogenesis of immune-mediated diseases. The associations between IL-12B gene variants and diseases such as type 1 diabetes (Morahan et al, 2001), asthma (Morahan et al, 2002), malaria (Marquet et al, 2008;Naka et al, 2009), and hepatitis C (Mueller et al, 2004;Hegazy et al, 2008) are well documented. Most gene association studies, however, were reported for Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%